THE IMPACT OF INFLATION ON CONSUMER SPENDING HABITS AND BUSINESS STRATEGIES (International journal of artificial intelligence, 2024)
Almost every part of our lives is impacted by inflation, which gradually raises the cost of products and services. This article looks at how inflation changes how people spend their money and how businesses plan their strategies. The way people decide what to buy is directly affected by inflation, which raises the prices of goods and services in general. When prices go up, people usually spend less on things they don't have to and more on things they do need. Businesses react to rising costs by changing their price tactics and supply lines. To attract and keep customers, they may also run sales or offer cheaper options. Secondary data, like reports and case studies, and primary data, like a survey of Uzbekistan customers, are both used in the study. The results show that when prices go up, people change how they spend their money, putting basic wants first and cutting back on things that aren't necessary. Businesses are responding by raising prices or putting out items that are good value for money. Furthermore, the study shows that both individuals and businesses need to adjust to changing economic situations to stay financially stable and successful.